Prevalence of Bacterial Urinary Tract Infections and Associated Factors among Patients Attending Hospitals in Bushenyi District, Uganda - Martin Odoki; Adamu Almustapha Aliero; Julius Tibyangye; Josephat Nyabayo Maniga; Eddie Wampande; Charles Drago Kato; Ezera Agwu; Joel Bazira (International Journal of Microbiology)
Urinary tract infections (UTIs) are one of the major causes of morbidity and comorbidities in patients with underlying conditions, and it accounts for the majority of the reasons for hospital visit globally. Sound knowledge of factors associated with UTI may allow timely intervention that can easily bring the disease under control. This study was designed to determine the prevalence of UTI by isolating and characterizing the different bacterial etiological agents and to evaluate the factors associated with UTI. In this cross-sectional study, a total of 267, clean catch midstream urine (MSU) samples were collected aseptically and analyzed using standard microbiology methods. Data for the factors associated with UTI were obtained by use of questionnaires and standard laboratory tests for selected underlying conditions. The study revealed 86/267 (32.2%) UTI prevalence among patients attending hospitals in Bushenyi District, Uganda. Escherichia coli was the most prevalent bacterial uropathogen with 36/86 (41.9%) followed by Staphylococcus aureus 27/86 (31.4%), Klebsiella pneumoniae 10/86 (11.6%), Klebsiella oxytoca 6/86 (7.0%), Proteus mirabilis 3/86 (3.5%), Enterococcus faecalis 3/86 (3.5%), and Proteus vulgaris 1/86 (1.2%). This study has demonstrated that age ≤19 years, female gender, married individuals, genitourinary tract abnormalities, diabetes, hospitalization, indwelling catheter <6 days, and indwelling catheter >6 days had statistically significant relationships (p<0.05) with UTI. Screening for UTI in hospitalized patients, female gender, married individuals, genitourinary tract abnormalities, indwelling catheter, and diabetics should be adopted.